(untitled) (Swiss Medical Weekly, 2016)
Statins are the cornerstone of the management of dyslipidaemias and prevention of cardiovascular disease. Although statins are, overall, safe and well tolerated, adverse events can occur and constitute an important barrier to maintaining long-term adherence to statin treatment. In patients who cannot tolerate statins, alternative treatments include switch to another statin, intermittent-dosage regimens and non-statin lipid-lowering medications. Nonetheless, a high proportion of statin-intolerant patients are unable to achieve recommended low-density lipoprotein (LDL) cholesterol goals, thereby resulting in substantial residual cardiovascular risk. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a protease implicated in LDL receptor degradation and plays a central role in cholesterol metabolism. In recent studies, PCSK9 inhibition by means of monoclonal antibodies achieved LDL cholesterol reductions of 50% to 70% across various patient populations and background lipid-lowering therapies, while maintaining a favourable safety profile. The efficacy and safety of the monoclonal antibodies alirocumab and evolocumab were confirmed in statin-intolerant patients, indicating that PCSK9 inhibitors represent an attractive treatment option in this challenging clinical setting. PCSK9 inhibitors recently received regulatory approval for clinical use and may be considered in properly selected patients according to current consensus documents, including patients with statin intolerance. In this review we summarise current evidence regarding diagnostic evaluation of statin-related adverse events, particularly statin-associated muscle symptoms, and we discuss current recommendations on the management of statin-intolerant patients. In view of emerging evidence of the efficacy and safety of PCSK9 inhibitors, we further discuss the role of monoclonal PCSK9 antibodies in the management of statin-intolerant hypercholesterolaemic patients.